Conformable Generalized Convolution on Time Scales - Georgiev, Svetlin G.; Chhatraband, Sneha M.; Thange, Tukaram G. (Discontinuity, Nonlinearity, and Complexity, 2026)
This paper introduces the concept of generalized conformable shift (delay) for the functions defined on an entire time scales by formulating the concept of generalized conformable shifting problem. We establish the existence of solutions and use this framework to define the generalized conformable convolution. A generalized conformable convolution theorem is then proved.